Efektifitas Pendidikan dan Pelatihan Daring untuk Penanggulangan Wabah pada Tim Aksi Gerak Cepat - Nur Alvira Pascawati; Febriana Emilda; Tumiat Tumiat; Timuryani Nugraheni; Darwani Darwani; Cahya Prihantama; Andri Setyo Dwi Nugroho (Universitas Faletehan, 2025)
Ministerial Regulation No. 1501 of 2010, Article 21(2), highlights the formation of a Rapid Action Team (RAT) as a part of Indonesia's outbreak control strategies. However, due to the massive spread and increase in Covid-19 cases, the education and training for RAT was carried out online. This study aims to identify determinant factors influencing the effectiveness of education and training using the online method for RAT community health centers. It employed a quasi-experimental design one-group pretest-posttest. The sample consisted of all training participants, totaling 60 individuals, from 12 health centers in the Special Region of Yogyakarta. Data analysis involved both simple and multiple linear regression tests. Research findings indicated that: 1) a significant difference existed in participants' knowledge scores before and after receiving education and training using the online method; 2) Determinant factors related to effectiveness included the quality of assignments, participant satisfaction with facilitator performance, and participant engagement. Continuation of online education and training methods can be achieved through ongoing monitoring of task quality, participant engagement, and facilitator performance. Technical challenges can be addressed by recording activities, testing content, and preparing contingency plans